Metakaolinite-based regenerated geopolymer prepared from construction waste and preparation method thereof
By studying the effect of regenerated fine powder on the properties of metakaolinite-based polymers, a metakaolinite-based regenerated geopolymer and its preparation method are provided, which solves the problem of low resource conversion rate in the existing technology and achieves Efficient construction waste recycling and sustainable development.
Patent Information
- Application Number
- CN202310670492.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-07
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-06-07
AI Technical Summary
In the prior art, there are few researches on regenerated geopolymers, especially the application of geopolymer concrete based on kaolinite substrates and regenerated fine aggregates has not been fully explored, resulting in a low resource conversion rate.
Through the effects of the intensity of regenerative fine powder and the impact of the condensation time and anti -compressive performance of the polymer base of the Gaogaolong Stone Base, combined with the testing test, it provides a kind of polymer and regenerative places for building waste preparation. Its preparation methods include a specific component distribution ratio and preparation steps.
It achieves a reasonable setting time and high compressive strength of the metakaolinite-based regenerated geopolymer, reduces the overall cost of the material, has significant economic benefits and high value-added application potential, and at the same time meets the sustainable development of the construction industry. need.
Smart Images

Figure CN116835916B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a metakaolinite-based regenerated geopolymer prepared from construction waste and a preparation method thereof. Background Art
[0002] The CO2 emissions from the building materials industry account for 18% of the country's total carbon emissions, while the CO2 emissions from the cement industry account for about 65% of the building materials industry. In order to reduce the carbon footprint of the building materials industry, especially cementitious materials, the development of alternative cementitious materials to Portland cement (OPC) is an important way.
[0003] Geopolymer is an amorphous cementitious material formed by the polymerization of SiO4 tetrahedron and AlO4 tetrahedron through the shared oxygen space to form a spatial network structure. It has a three-dimensional stable and orderly network structure. Its polymerization reaction is essentially different from the hydration process of ordinary Portland cement. Therefore, geopolymer has many advantages in terms of performance, mainly manifested as: high mechanical strength, excellent corrosion resistance, excellent durability, good high temperature resistance and fire resistance, and strong heavy metal ion curing ability. In recent years, geopolymer has received great attention due to its excellent mechanical properties, durability and fire resistance, and due to its low CO2 emissions during its preparation process, it has multiple functionalities. Therefore, geopolymer has great potential to replace OPC.
[0004] Current research shows that fly ash, slag, and kaolinite are common precursors for preparing geopolymers. Kaolinite is a typical 1:1 dioctahedral clay mineral. Due to its high volcanic ash activity, kaolinite is used in the preparation of geopolymers, and kaolinite-based geopolymers show more favorable properties than other alkali-activated materials. Due to its simple chemical composition, kaolinite is widely used in the preparation of geopolymers and the analysis of geopolymer mechanisms.
[0005] With the maturity and development of technology, geopolymers will inevitably be promoted and used, and after promotion, a lot of construction waste based on geopolymers will be formed. At present, many studies are based on the recycling of ordinary Portland cement construction waste. A large number of studies have shown that recycled concrete prepared with recycled coarse aggregate can be widely used in most non-structural load-bearing structures, such as roadbeds and pavements; recycled fine aggregate can also be used to prepare recycled mortar, such as plaster mortar, non-load-bearing masonry mortar and road base materials, realizing the recycling of construction waste. Research conducted in recent years has shown the possible uses and acceptable performance of recycled concrete aggregates, broken bricks, and recycled asphalt pavements as materials for recycled aggregates. The use of different types of recycled materials has been proven to be an excellent substitute for natural aggregates without greatly losing infrastructure performance.
[0006] At present, there are few studies on recycled geopolymers at home and abroad, and only fly ash-based geopolymer concrete and recycled coarse aggregate are studied. The application of other-based geopolymer concrete and recycled fine aggregate is temporarily vacant. At the same time, only recycled coarse aggregate is used, and recycled fine aggregate is not mixed, so the resource conversion rate is low. Therefore, in view of the shortcomings of the existing technology, it is of great necessity to provide a kaolinite-based recycled geopolymer prepared from construction waste and its preparation method, so as to provide data for the subsequent research on geopolymer recycled concrete and lay the foundation for the efficient utilization of geopolymer construction waste. Summary of the invention
[0007] The purpose of the present invention is to provide a metakaolinite-based recycled geopolymer prepared from construction waste and a preparation method thereof in view of the deficiencies of the prior art. The effects of the strength of recycled fine powder raw materials and the replacement rate of recycled fine powder on the setting time and compressive properties of the metakaolinite-based polymer are experimentally studied, and combined with characterization tests, a metakaolinite-based recycled geopolymer prepared from construction waste and a preparation method thereof are obtained.
[0008] In order to achieve the above objectives, the present invention is implemented through the following technical means.
[0009] Provided are a metakaolinite-based recycled geopolymer prepared from construction waste and a preparation method thereof. The geopolymer comprises the following components, measured by mass: 10-20 parts of metakaolin, 10-20 parts of sodium silicate, 8-18 parts of sodium hydroxide, 23-40 parts of deionized water, 0-28 parts of 10MPa recycled fine powder, 0-28 parts of 30MPa recycled fine powder, 0-2 parts of ordinary concrete recycled fine powder, and 0-2 parts of fly ash.
[0010] Generally, in the above technical solution, metakaolinite is used to ensure the overall strength of the metakaolinite-based polymer, and sodium hydroxide, sodium silicate and deionized water are used to prepare an alkaline solution to stimulate the metakaolinite to form a gelling material with a three-dimensional network structure. The interaction of each component ultimately forms a metakaolinite-based recycled geopolymer with excellent performance and is widely used in a variety of fields.
[0011] Furthermore, the metakaolinite is kaolinite powder calcined in air at 700° C. for 3 hours in a muffle furnace with a heating rate of 10° C. / min.
[0012] Furthermore, the regenerated fine powder is obtained by grinding the waste metakaolinite-based polymer samples with a crusher and sieving them through a 200-mesh sieve, and the waste geopolymer samples are divided into two batches according to the 28d compressive strength: 10 MPa and 30 MPa.
[0013] Furthermore, the kaolinite comes from Maoming, Guangdong, and the mass percentage of each oxide in its chemical composition is: Al2O3 (38.59%), SiO2 (58.22%), Fe2O3 (0.89%), K2O (0.87%), MgO (0.21%), SO3 (0.37%), CaO (0.02%), TiO2 (0.53%) and the remainder of other impurities (0.30%).
[0014] Furthermore, the sodium silicate is a sodium silicate solution, in which the chemical composition includes 8.9% by mass of Na2O and 28.8% by mass of SiO2, and the modulus is 3.3.
[0015] Furthermore, the sodium hydroxide is a solid particle with a mass purity of ≥96%.
[0016] Furthermore, the deionized water is process purification water provided by the laboratory. Optionally, the deionized water is distilled water and / or deionized water, wherein the deionized water is prepared by a reverse osmosis method.
[0017] Furthermore, the mass percentage of each oxide in the chemical composition of the 10MPa regenerated fine powder is: SiO2 (43.93%), Al2O3 (34.95%), Na2O (17.86%), K2O (0.65%), Fe2O3 (0.47), MgO (0.43%), SO3 (0.28%), TiO2 (0.37%), CaO (0.04%) and the remainder of other impurities (1.02%).
[0018] Furthermore, the mass percentage of each oxide in the chemical composition of the 30MPa regenerated fine powder is: SiO2 (49.77%), Al2O3 (31.12%), Na2O (15.53%), K2O (0.55%), Fe2O3 (0.43), MgO (0.54%), SO3 (1.17%), TiO2 (0.36%), CaO (0.02%) and the remainder of other impurities (0.51%).
[0019] Furthermore, a metakaolinite-based regenerated geopolymer prepared from construction waste and a preparation method thereof are provided, comprising the following steps:
[0020] (1) Prepare the materials by weighing sodium silicate, sodium hydroxide and deionized water according to their mass percentages;
[0021] (2) preparing an alkaline solution by adding sodium hydroxide particles to deionized water, stirring evenly, and leaving the mixture for 24 hours for use, and then adding sodium silicate solution and stirring evenly to prepare an alkaline solution;
[0022] (3) Weigh the metakaolinite, 10MPa regenerated fine powder, and 30MPa regenerated fine powder according to the mass fraction to prepare the materials;
[0023] (4) Pour the weighed metakaolinite (kaolinite calcined in a muffle furnace at 700°C in air for 3 hours) into a beaker for later use;
[0024] (5) adding 10 MPa regenerated fine powder and / or 30 MPa regenerated fine powder to the metakaolin obtained above and stirring evenly to prepare a mixed raw material (this step can be omitted in the embodiment without the regenerated fine powder blank control group);
[0025] (6) Pour the alkaline solution into a beaker and stir manually until a uniform paste is formed to obtain a freshly mixed metakaolinite-based recycled geopolymer;
[0026] (7) Place the newly mixed kaolinite-based recycled geopolymer into a plastic mold and place it on a vibrator to vibrate for 2 minutes to expel bubbles. Place it in a room at 20°C ± 5°C for curing for 28-30 days.
[0027] The metakaolinite-based recycled geopolymer has a setting time of 68-220 minutes and a 28-day compressive strength of 41.3-46.55 MPa.
[0028] The obtained metakaolinite-based recycled geopolymer is applied to non-load-bearing components of buildings, or foundation cushions of buildings or road bases.
[0029] The beneficial effects of the present invention are:
[0030] (1) The metakaolinite-based recycled geopolymer provided by the present invention has a setting time within a reasonable range, which is convenient for controlling the construction progress and construction period;
[0031] (2) Compared with common geopolymers, the kaolinite-based recycled geopolymer provided by the present invention can reduce the comprehensive cost of the recycled geopolymer material by adding recycled fine powder, has significant economic benefits, and has considerable application prospects.
[0032] (3) The metakaolinite-based recycled geopolymer provided by the present invention uses a metakaolinite precursor, which has a wide source and simple composition, making it easier to study the effect of recycled fine powder on its internal microstructure, thereby confirming its macroscopic compressive resistance.
[0033] (4) The metakaolinite-based recycled geopolymer provided by the present invention has a certain compressive strength, which can meet the requirements of building strength, and its three-dimensional network structure can show excellent durability;
[0034] (5) The addition of recycled fine powder in an amount of less than 30% into the kaolinite-based recycled geopolymer provided by the present invention shows a positive effect on the strength of the geopolymer, and the two different fine powders have a mutually promoting effect, have a certain micro-aggregate filling effect and volcanic ash effect, play a role in the recycling of construction waste, and have the potential for high value-added applications; the recycled fine powder can exert a micro-aggregate effect, promote clinker hydration and the volcanic ash reaction activity of the admixture, enhance the adhesion between the recycled fine aggregate and the geopolymer cementitious material, and improve the strength of the recycled geopolymer.
[0035] (6) Compared with the two-grinding-one-burning process of cement production, the kaolinite-based recycled geopolymer provided by the present invention has low energy consumption in the preparation process, low CO2 emissions, and a wide range of raw materials. Studies have shown that geopolymer can replace silicate cement to reduce energy consumption by 60-70% and CO2 emissions by 70-80%, meet the sustainable development of the construction industry, and alleviate the ecological and environmental crisis. It is a green and environmentally friendly building material. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The present invention is a flow chart of the preparation method of kaolinite-based polymer.
[0037] Figure 2 The present invention is a flow chart of the preparation method of kaolinite-based regenerated geopolymer.
[0038] Figure 3 This is the result diagram of the setting time of kaolinite-based recycled geopolymer.
[0039] Figure 4 This is the compressive strength result diagram of kaolinite-based recycled geopolymer.
[0040] Figure 5 This is the SEM image result of kaolinite-based recycled geopolymer with 10MPa recycled fine powder.
[0041] Figure 6 This is the SEM image result of kaolinite-based recycled geopolymer with 30MPa recycled fine powder.
[0042] Figure 7 This is the SEM image result of kaolinite-based recycled geopolymer combined with 10MPa and 30MPa recycled fine powder. DETAILED DESCRIPTION
[0043] In order to express the present invention more clearly, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. Example 1
[0044] This embodiment relates to a metakaolinite-based regenerated geopolymer prepared using construction waste fine aggregate and a preparation method thereof, comprising the following steps:
[0045] The formula (in parts by mass) is designed as follows: (1) 20 parts of metakaolin; (2) 11 parts of sodium silicate; (3) 9 parts of sodium hydroxide; (4) 23 parts of deionized water; (5) 0 parts of 10 MPa regenerated fine powder or 30 MPa regenerated fine powder.
[0046] The metakaolinite is kaolinite calcined in a muffle furnace in air at 700° C. for 3 hours at a heating rate of 10° C. / min.
[0047] The sodium silicate is a sodium silicate solution, in which the chemical composition includes 8.9% by mass of Na2O and 28.8% by mass of SiO2, and the modulus is 3.3.
[0048] Wherein, the sodium hydroxide is a solid particle with a mass purity of ≥96%.
[0049] The deionized water is specially provided for laboratory use.
[0050] The above materials are prepared according to the following steps to prepare a kaolinite-based regenerated geopolymer prepared from construction waste and a preparation method thereof, such as Figure 1 As shown, the following steps are included:
[0051] (1) Weigh the materials according to 11 parts of sodium silicate, 9 parts of sodium hydroxide, and 23 parts of deionized water. Use an electronic balance to weigh the materials. The weighing balance accuracy of the materials is ±0.01g;
[0052] (2) preparing an alkaline solution by adding 9 parts of sodium hydroxide particles to 23 parts of deionized water, stirring evenly, and leaving the mixture for 24 hours for use, and then adding 11 parts of sodium silicate solution and stirring evenly to prepare an alkaline solution;
[0053] (3) Weigh the material according to 20 parts of metakaolinite using an electronic balance with an accuracy of ±0.01 g;
[0054] (4) Pour 20 parts of kaolinite (calcined in a muffle furnace at 700°C in air for 3 hours) into a beaker for later use;
[0055] (5) Pour the alkaline solution into a beaker and stir manually until a uniform paste is formed to obtain a freshly mixed metakaolinite-based polymer;
[0056] (6) Place the newly mixed metakaolinite-based polymer into a plastic mold and place it on a vibrator to vibrate for 2 minutes to expel air bubbles. Place it in a room at 20°C ± 5°C for 28 days.
[0057] Since no 10 MPa regenerated fine powder or 30 MPa regenerated fine powder was added in Example 1, accounting for 0% of the total solid raw material mass, it was named G0. Example 2
[0058] This embodiment relates to a metakaolinite-based regenerated geopolymer prepared from construction waste and a preparation method thereof, comprising the following steps:
[0059] The formula (in parts by mass) is designed as follows: (1) 19 parts of metakaolin; (2) 11 parts of sodium silicate; (3) 9 parts of sodium hydroxide; (4) 23 parts of deionized water; and (5) 1 part of 10 MPa regenerated fine powder.
[0060] The metakaolinite is kaolinite calcined in a muffle furnace in air at 700° C. for 3 hours at a heating rate of 10° C. / min.
[0061] The sodium silicate is a sodium silicate solution, in which the chemical composition includes 8.9% by mass of Na2O and 28.8% by mass of SiO2, and the modulus is 3.3.
[0062] Wherein, the sodium hydroxide is a solid particle with a mass purity of ≥96%.
[0063] The deionized water is specially provided for laboratory use.
[0064] The above materials are prepared according to the following steps to prepare a kaolinite-based regenerated geopolymer prepared from construction waste and a preparation method thereof, such as Figure 2 As shown, the following steps are included:
[0065] (1) Weigh the materials according to 11 parts of sodium silicate, 9 parts of sodium hydroxide, and 23 parts of deionized water. Use an electronic balance to weigh the materials. The weighing balance accuracy of the materials is ±0.01g;
[0066] (2) preparing an alkaline solution by adding 9 parts of sodium hydroxide particles to 23 parts of deionized water, stirring evenly, and leaving the mixture for 24 hours for use, and then adding 11 parts of sodium silicate solution and stirring evenly to prepare an alkaline solution;
[0067] (3) Weigh the material according to 19 parts of metakaolin and 1 part of 10MPa recycled fine powder. Use an electronic balance to weigh the material. The weighing balance accuracy of the material is ±0.01g;
[0068] (4) Pour 19 parts of metakaolinite (kaolinite calcined in a muffle furnace at 700°C in air for 3 hours) into a beaker for later use;
[0069] (5) adding 1 part of 10 MPa regenerated fine powder to 19 parts of metakaolin and stirring evenly to prepare a mixed raw material;
[0070] (6) Pour the alkaline solution into a beaker and stir manually until a uniform paste is formed to obtain a freshly mixed metakaolinite-based recycled geopolymer;
[0071] (7) Place the newly mixed kaolinite-based recycled geopolymer into a plastic mold and place it on a vibrator to vibrate for 2 minutes to expel bubbles. Place it in a room at 20°C ± 5°C for 28 days.
[0072] Since the geopolymer in Example 2 can be calculated by mass fraction to obtain 10MPa regenerated fine powder / total solids = 5%, and the strength of the regenerated fine powder raw material is 10MPa, it is named G1-R 5% . Example 3
[0073] This embodiment involves the components and mass fractions of the kaolinite-based recycled geopolymer prepared using construction waste fine aggregate, and the preparation method of the kaolinite-based recycled geopolymer is the same as that of Example 2, except that the mass fraction of 10MPa recycled fine powder is replaced by 2 parts.
[0074] Since the geopolymer in Example 3 can be calculated by mass fraction to obtain 10MPa regenerated fine powder / total solids = 10%, and the strength of the regenerated fine powder raw material is 10MPa, it is named G1-R 10% . Example 4
[0075] This embodiment involves the components and mass parts of the kaolinite-based recycled geopolymer prepared using construction waste fine aggregate, and the preparation method of the kaolinite-based recycled geopolymer is the same as that of Example 2, except that the mass part of 10MPa recycled fine powder is replaced by 6 parts.
[0076] Since the geopolymer in Example 4 can be calculated by mass fraction to obtain 10MPa regenerated fine powder / total solids = 30%, and the strength of the regenerated fine powder raw material is 10MPa, it is named G1-R 30% . Example 5
[0077] This embodiment involves the components and mass parts of the kaolinite-based recycled geopolymer prepared using construction waste fine aggregate, and the preparation method of the kaolinite-based recycled geopolymer is the same as that of Example 2, except that the mass part of 10MPa recycled fine powder is replaced by 10 parts.
[0078] Since the geopolymer in Example 5 can be calculated by mass fraction to obtain 10MPa regenerated fine powder / total solids = 50%, and the strength of the regenerated fine powder raw material is 10MPa, it is named G1-R 50% . Example 6
[0079] This embodiment involves the components and mass parts of the kaolinite-based recycled geopolymer prepared using construction waste fine aggregate, and the preparation method of the kaolinite-based recycled geopolymer is the same as that of Example 2, except that the mass part of 10MPa recycled fine powder is replaced by 20 parts.
[0080] Since the geopolymer in Example 6 can be calculated based on the mass fraction formula to obtain 10 MPa recycled fine powder / total solids = 100%, and the strength of the recycled fine powder raw material is 10 MPa, it is named G1-R100%. Example 7
[0081] This embodiment relates to a metakaolinite-based regenerated geopolymer prepared using construction waste fine aggregate and a preparation method thereof, comprising the following steps:
[0082] The formula (in parts by mass) is designed as follows: (1) 19 parts of metakaolin; (2) 11 parts of sodium silicate; (3) 9 parts of sodium hydroxide; (4) 23 parts of deionized water; and (5) 1 part of 30 MPa regenerated fine powder.
[0083] The metakaolinite is kaolinite calcined in a muffle furnace in air at 700° C. for 3 hours at a heating rate of 10° C. / min.
[0084] The above materials are prepared according to the following steps to prepare a kaolinite-based regenerated geopolymer prepared from construction waste and a preparation method thereof, such as Figure 2 As shown, the following steps are included:
[0085] (1) Weigh the materials according to 11 parts of sodium silicate, 9 parts of sodium hydroxide, and 23 parts of deionized water. Use an electronic balance to weigh the materials. The weighing balance accuracy of the materials is ±0.01g;
[0086] (2) preparing an alkaline solution by adding 9 parts of sodium hydroxide particles to 23 parts of deionized water, stirring evenly, and leaving the mixture for 24 hours for use, and then adding 11 parts of sodium silicate solution and stirring evenly to prepare an alkaline solution;
[0087] (3) Weigh the material according to 19 parts of metakaolin and 1 part of 30MPa recycled fine powder. Use an electronic balance to weigh the material. The weighing balance accuracy of the material is ±0.01g;
[0088] (4) Pour 19 parts of metakaolinite (kaolinite calcined in a muffle furnace at 700°C in air for 3 hours) into a beaker for later use;
[0089] (5) adding 1 part of 30 MPa regenerated fine powder to 19 parts of metakaolin and stirring evenly to prepare a mixed raw material;
[0090] (6) Pour the alkaline solution into a beaker and stir manually until a uniform paste is formed to obtain a freshly mixed metakaolinite-based recycled geopolymer;
[0091] (7) Place the newly mixed kaolinite-based recycled geopolymer into a plastic mold and place it on a vibrator to vibrate for 2 minutes to expel bubbles. Place it in a room at 20°C ± 5°C for 28 days.
[0092] Since the geopolymer in Example 7 can be calculated by mass fraction to obtain 30MPa regenerated fine powder / total solids = 5%, and the strength of the regenerated fine powder raw material is 30MPa, it is named G2-R 5% . Example 8
[0093] This embodiment relates to a kaolinite-based regenerated geopolymer prepared from construction waste and its preparation method, the components and mass parts thereof, and the preparation method of the kaolinite-based regenerated geopolymer are the same as those in Example 7, except that the mass part of 30MPa regenerated fine powder is replaced by 2 parts.
[0094] Since the geopolymer in Example 8 can be calculated by mass fraction to obtain 30MPa regenerated fine powder / total solids = 10%, and the strength of the regenerated fine powder raw material is 30MPa, it is named G2-R 10% . Example 9
[0095] This embodiment relates to a kaolinite-based regenerated geopolymer prepared from construction waste and its preparation method, components and mass parts thereof, and the preparation method of kaolinite-based regenerated geopolymer is the same as that in Example 7, except that the mass part of 30MPa regenerated fine powder is replaced by 6 parts.
[0096] Since the geopolymer in Example 9 can be calculated by mass fraction to obtain 30MPa regenerated fine powder / total solids = 30%, and the strength of the regenerated fine powder raw material is 30MPa, it is named G2-R 30% . Example 10
[0097] This embodiment relates to a kaolinite-based regenerated geopolymer prepared from construction waste and its preparation method, the components and mass parts thereof, and the preparation method of the kaolinite-based regenerated geopolymer are the same as those in Example 7, except that the mass part of 30MPa regenerated fine powder is replaced by 10 parts.
[0098] Since the geopolymer in Example 10 can be calculated by mass fraction to obtain 30MPa regenerated fine powder / total solids = 50%, and the strength of the regenerated fine powder raw material is 30MPa, it is named G2-R 50% . Embodiment 11
[0099] This embodiment relates to a kaolinite-based regenerated geopolymer prepared from construction waste and its preparation method, the components and mass parts thereof, and the kaolinite-based regenerated geopolymer preparation method are the same as those in Example 7, except that the mass parts of 30MPa regenerated fine powder are replaced by 20 parts.
[0100] Since the geopolymer in Example 11 can be calculated by mass fraction to obtain 30MPa regenerated fine powder / total solids = 100%, and the strength of the regenerated fine powder raw material is 30MPa, it is named G2-R 100% . Example 12
[0101] This embodiment relates to a metakaolinite-based regenerated geopolymer prepared using construction waste fine aggregate and a preparation method thereof, comprising the following steps:
[0102] The formula (in parts by mass) is designed as follows: (1) 18 parts of metakaolin; (2) 11 parts of sodium silicate; (3) 9 parts of sodium hydroxide; (4) 23 parts of deionized water; (5) 1 part of 10 MPa regenerated fine powder; (6) 1 part of 30 MPa regenerated fine powder.
[0103] The metakaolinite is kaolinite calcined in a muffle furnace in air at 700° C. for 3 hours at a heating rate of 10° C. / min.
[0104] The above materials are prepared according to the following steps to prepare a kaolinite-based regenerated geopolymer prepared from construction waste and a preparation method thereof, such as Figure 2 As shown, the following steps are included:
[0105] (1) Weigh the materials according to 11 parts of sodium silicate, 9 parts of sodium hydroxide, and 23 parts of deionized water. Use an electronic balance to weigh the materials. The weighing balance accuracy of the materials is ±0.01g;
[0106] (2) preparing an alkaline solution by adding 9 parts of sodium hydroxide particles to 23 parts of deionized water, stirring evenly, and leaving the mixture for 24 hours for use, and then adding 11 parts of sodium silicate solution and stirring evenly to prepare an alkaline solution;
[0107] (3) Weigh the materials according to 18 parts of metakaolin, 1 part of 10MPa recycled fine powder, and 1 part of 30MPa recycled fine powder. Use an electronic balance to weigh the materials. The weighing balance accuracy of the materials is ±0.01g;
[0108] (4) Pour 18 parts of metakaolinite (kaolinite calcined in a muffle furnace at 700°C in air for 3 hours) into a beaker for later use;
[0109] (5) adding 1 part of 10 MPa regenerated fine powder and 1 part of 30 MPa regenerated fine powder to 18 parts of metakaolin and stirring evenly to prepare a mixed raw material;
[0110] (6) Pour the alkaline solution into a beaker and stir manually until a uniform paste is formed to obtain a freshly mixed metakaolinite-based recycled geopolymer;
[0111] (7) Place the newly mixed kaolinite-based recycled geopolymer into a plastic mold and place it on a vibrator to vibrate for 2 minutes to expel bubbles. Place it in a room at 20°C ± 5°C for 28 days.
[0112] Since the geopolymer in Example 12 can obtain two kinds of recycled fine powder / total solids = 10% by mass, it is named G3-R 10% . Example 13
[0113] This embodiment relates to a kaolinite-based recycled geopolymer prepared from construction waste and its preparation method, the components and mass parts thereof, and the kaolinite-based recycled geopolymer preparation method are the same as those in Example 12, except that the mass parts of 10MPa and 30MPa recycled fine powders are replaced with 3 parts.
[0114] Since the geopolymer in Example 13 can obtain two kinds of recycled fine powder / total solids = 30% by mass, it is named G3-R 30% . Embodiment 14
[0115] This embodiment relates to a kaolinite-based recycled geopolymer prepared from construction waste and its preparation method, the components and mass parts thereof, and the kaolinite-based recycled geopolymer preparation method are the same as those in Example 12, except that the mass parts of 10MPa and 30MPa recycled fine powders are replaced by 5 parts.
[0116] Since the geopolymer in Example 14 can obtain two types of recycled fine powder / total solids = 50% by mass, it is named G3-R 50% . Embodiment 15
[0117] This embodiment relates to the components and mass parts of a kaolinite-based recycled geopolymer prepared using ordinary concrete recycled fine powder, and the preparation method of the kaolinite-based recycled geopolymer is the same as that in Example 12, except that the mass parts of 10MPa / 30MPa recycled fine powder are replaced by 2 parts of ordinary concrete recycled fine powder.
[0118] Since the geopolymer in Example 15 can be calculated by mass fraction to obtain ordinary concrete recycled fine powder / total solids = 10%, it is named G C -R 10% . Example 16
[0119] This embodiment relates to a kaolinite-based regenerated geopolymer prepared using fly ash, and its components and mass fractions, and the method for preparing the kaolinite-based regenerated geopolymer are the same as those in Example 12, except that the mass fraction of 10MPa / 30MPa regenerated fine powder is replaced by 2 parts of fly ash.
[0120] Since the geopolymer in Example 16 is calculated by mass fraction to obtain fly ash / total solids = 10%, it is named G F -R 10% .
[0121] The present invention measures the initial and final setting time of the metakaolinite-based recycled geopolymer with reference to "Test Method for Water Consistency, Setting Time and Stability of Cement Standard Consistency" (GB / T1346-2011), and the test instrument is a Vicat instrument; drawing on the method for testing the strength of cement mortar, a cube with a specimen size of 20mm×20mm×20mm is selected to perform a compression test on the metakaolinite-based recycled geopolymer, and its compressive strength is measured, and the test instrument is a microcomputer-controlled electronic universal testing machine.
[0122] The determination methods of the technical indicators of the present invention are all standard determination methods in the field. For details, please refer to the latest national standards, unless otherwise specified.
[0123] Figure 3 This is the result of the setting time of the kaolinite-based recycled geopolymer. Figure 3 It can be found that with the increase of the amount of recycled fine powder at 10MPa or 30MPa, except for G 10 -R 10% In addition, the initial setting and final setting times of the two groups of geopolymer slurries with different raw material strengths gradually prolonged, and during the sample preparation process, with the increase of the substitution rate, the geopolymerization reaction in the experimental process was significantly accelerated and the duration was short. This shows that the fine powder has poor activity and the geopolymerization reaction is weak. The initial setting and final setting times of the geopolymer slurry in the blank group (68 and 103 minutes, respectively) are much shorter than those of the slurry with 100% fine powder replacement rate (which cannot be initially set at room temperature), indicating that the recycled fine powder has greatly delayed the polymerization process of kaolinite, thereby inhibiting the coagulation and hardening of the slurry. The overall initial and final setting times of the composite fine powder group are greater than those of the G 10 Group and less than G 30 Among the groups, the setting time of ordinary concrete group is the longest, which is greater than that of fly ash group.
[0124] Figure 4The compressive strength results of kaolinite-based recycled geopolymers. With the increase of fine powder replacement rate, the compressive strength of the three types of samples showed a gradual increase and then a gradual decrease. The 28-day compressive strength of the geopolymer containing 10% recycled fine powder in G1 (41.31MPa) is 2.2% higher than that of the geopolymer without fine powder (40.43MPa). The 28-day compressive strength of the geopolymer containing 30% recycled fine powder in G2 (44.26MPa) is 9.47% higher than that of the geopolymer without fine powder (40.43MPa). The 28d compressive strength of the geopolymer containing 10% recycled fine powder in G3 (46.55MPa) is 12.68% higher than that of G1 (41.31MPa) and 5.17% higher than that of G2 (44.26MPa). The fine powder replacement rate between 10% and 50% has a relatively weak adverse effect on the mechanical properties of the geopolymer. G1-R 50% The 28-day compressive strength of the sample (30.23MPa) is higher than that of G1-R 10% Down 36.65%, G2-R 50% The 28-day compressive strength of the sample (24.79MPa) is higher than that of G2-R 10% A decrease of 43.99%. C -R 10% The 28-day compressive strength of the sample (34.2MPa) is higher than that of G3-R 10% (46.55MPa) decreased by 26.53%, G F -R 10% The 28-day compressive strength of the sample (41.7MPa) is higher than that of G3-R 10% It decreased by 10.42%. This indicates that adding a small amount (less than 30%) of recycled fine powder can improve the mechanical properties of kaolinite-based polymers: composite fine powder has a promoting effect on the compressive strength of recycled geopolymers.
[0125] Figure 5 and Figure 6 This is the SEM image result of the kaolinite-based recycled geopolymer. 10% The small pores are filled with unreacted layered metakaolinite, so G1-R 10% The compressive strength is slightly higher than G0. G1-R 50% Large cracks appear under low magnification, and high magnification SEM images show that the geopolymer matrix is thicker than G1-R 100% However, a large amount of unreacted layered metakaolinite is embedded in the geopolymer matrix, destroying the G1-R 50% The uniform microstructure of G1-R 100%The SEM images of the geopolymers show many macropores, which are derived from the air trapped in the geopolymer matrix, and the geopolymer matrix shows loose dispersion changes. Therefore, the recycled geopolymer with a replacement rate of 100% shows a very low compressive strength.
[0126] Existing studies have shown that geopolymers are inorganic gelling materials with a three-dimensional network structure formed by silicon-oxygen tetrahedrons and aluminum-oxygen tetrahedrons through shared oxygen. The metakaolinite-based recycled geopolymer prepared in this experiment has a three-dimensional structure formed by silicon-oxygen tetrahedrons and aluminum-oxygen tetrahedron units through shared oxygen through XRD, FTIR, and EDS characterization tests, and the recycled fine powder can play a filling role in geopolymers. Compared with the low-strength van der Waals bonds and hydrogen bonds of cement-based materials, the connecting bonds between silicon-oxygen tetrahedrons and aluminum-oxygen tetrahedrons in its structure are covalent bonds, which have higher strength.
[0127] In summary, it can be found that the strength of the fine powder raw material does not significantly change the microstructure and mechanical properties of the geopolymer, and the negative impact of the substitution rate on the mechanical properties is more significant than the strength of the fine powder raw material. When the replacement rate of the recycled fine powder in the two groups of recycled geopolymer samples is low, both show a relatively dense microstructure and high compressive strength. And with a small increase in the substitution rate, the 7d and 28d compressive strengths are further enhanced. The fine powder itself is not very active, but it has a certain micro-aggregate filling effect and volcanic ash effect, and has the potential for high value-added applications. It can be seen that the kaolinite-based recycled geopolymer of the present invention can not only meet certain strength requirements, but also reduce costs to achieve the recycling and reuse of construction waste.
[0128] The above is only a detailed description of the preferred feasible embodiments of the present invention, and is not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A metakaolinite-based regenerated geopolymer prepared from construction waste, characterized in that: The raw material components include, by weight: 10-20 parts of metakaolin, 10-20 parts of sodium silicate, 8-18 parts of sodium hydroxide, 23-40 parts of deionized water, 0-28 parts of 10MPa recycled fine powder, 0-28 parts of 30MPa recycled fine powder, 0-2 parts of ordinary concrete recycled fine powder, and 0-2 parts of fly ash; the recycled fine powder is obtained by grinding a waste metakaolin-based polymer sample with a crusher and sieving it through a 200-mesh sieve; the waste geopolymer sample has a 28d compressive strength of 10MPa and 30MPa, respectively, to obtain the corresponding 10MPa recycled fine powder and 30MPa recycled fine powder; Taking metakaolinite, 10MPa regenerated fine powder and 30MPa regenerated fine powder as the total solids, the addition amount of 10MPa regenerated fine powder is 5% of the total solids, and the addition amount of 30MPa regenerated fine powder is 5% of the total solids; Or the amount of 10MPa regenerated fine powder added is 0, and the amount of 30MPa regenerated fine powder added is 5%-10% of the total solids; The mass percentage of each oxide in the chemical composition of the 10MPa regenerated fine powder is: SiO2 43.93%, Al2O3 34.95%, Na2O 17.86%, K2O 0.65%, Fe2O3 0.47, MgO 0.43%, SO3 0.28%, TiO2 0.37%, CaO 0.04%, and the balance is other impurities; The mass percentage of each oxide in the chemical composition of 30MPa regenerated fine powder is: SiO2 49.77%, Al2O3 31.12%, Na2O 15.53%, K2O 0.55%, Fe2O3 0.43, MgO 0.54%, SO3 1.17%, TiO2 0.36%, CaO 0.02% and the remainder are other impurities.
2. The metakaolinite-based regenerated geopolymer prepared from construction waste according to claim 1, characterized in that: The metakaolinite is obtained by calcining kaolinite powder in a muffle furnace in air at 700° C. for 3 hours, with a heating rate of 10° C. / min.
3. The metakaolinite-based regenerated geopolymer prepared from construction waste according to claim 1, characterized in that: The mass percentage of each oxide in its chemical composition is: Al2O3 38.59%, SiO2 58.22%, Fe2O3 0.89%, K2O 0.87%, MgO 0.21%, SO3 0.37%, CaO 0.02%, TiO2 0.53% and the remainder are other impurities.
4. The metakaolinite-based regenerated geopolymer prepared from construction waste according to claim 1, characterized in that: The metakaolinite-based recycled geopolymer has a setting time of 68-220 minutes and a 28-day compressive strength of 41.3-46.55 MPa.
5. A method for preparing the metakaolinite-based regenerated geopolymer prepared from construction waste according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Prepare the materials by weighing sodium silicate, sodium hydroxide and deionized water according to their mass percentages; (2) preparing an alkaline solution by adding sodium hydroxide particles to deionized water, stirring evenly, and leaving the mixture for 24 hours for use, and then adding sodium silicate solution and stirring evenly to prepare an alkaline solution; (3) preparing materials by weighing the metakaolinite obtained by calcining kaolinite in a muffle furnace at 700°C in air for 3 hours, the metakaolinite, 10MPa regenerated fine powder, and 30MPa regenerated fine powder according to their mass fractions; (4) Pour the weighed metakaolin into a beaker for later use, add 10 MPa regenerated fine powder and / or 30 MPa regenerated fine powder to the metakaolin and stir evenly to prepare a mixed raw material; (5) Pour the alkaline solution into a beaker and stir manually until a uniform paste is formed to obtain the newly mixed metakaolinite-based recycled geopolymer; (6) Place the newly mixed kaolinite-based recycled geopolymer into a plastic mold and place it on a vibrator to vibrate for 2 minutes to expel bubbles. Place it in a room at 20°C ± 5°C for curing for 28-30 days.
6. An application of metakaolinite-based regenerated geopolymer prepared from construction waste, characterized in that: The metakaolinite-based regenerated geopolymer prepared from construction waste is prepared by using the preparation method of any one of claims 1 to 4, or the metakaolinite-based regenerated geopolymer prepared from construction waste is prepared by using the preparation method of claim 5, and the metakaolinite-based regenerated geopolymer prepared from construction waste is applied to non-load-bearing components of buildings, or foundation cushion layers of buildings or road base layers.